Modeling the influence of inflation on the level of non-performing loans in Cyprus commercial banks - Ptasica, Tatjana (Technology audit and production reserves, 2018)
The object of this research is the commercial banks of Cyprus. The paper examines the impact of macroeconomic changes, in particular inflation, on the level of non-performing loans in commercial banks. The macroeconomic indicators studied include inflation rates. The research methodology is based on theoretical and methodological analysis of the scientific literature, statistical and econometric methods, as well as observation, comparative method, description, measurement, analysis and modeling. To develop a statistical model that represents the relationship between inflation rates and non-performing loans in Cyprus, the author uses simple linear correlation and data analysis methods such as the correlation coefficient and the determination coefficient. The research results show that the resulting econometric model is acceptable, since the determination coefficient is equal to 0.504, and inflation indicators are decisive for the level of non-performing loans. This is due to the fact that the correlation coefficient between these variables is –0.710, and according to the Chaddock scale the coupling magnitude is high. In addition, the correlation coefficient of inflation and non-performing loans in Cyprus is statistically significant, since the value of the correlation coefficient is beyond the limits of critical values of |0.468|. Also from the research results it is found that in the case of Cyprus, inflation rates are negatively associated with non-performing loans, since the resulting correlation coefficient is a negative number. The resulting model is not used to compile a short-term forecast, due to the insufficient value of the determination coefficient (50.4 %). In general, it is proposed that policy makers devote considerable attention to the determinants of non-performing loans, as the deteriorating conditions of non-performing loans will affect not only banking institutions, but also the general state of the financial system of Cyprus. The practical significance of the research cited in the work lies in the fact that the research results can be used as reference material for business, government and education.